Ritmo Circadiano de Triiodotironina (T3) e Tiroxina (T4) Plasmática em Ovelhas Ideal durante o Anestro Estacional - Velasquez, LFU (1997)
The objective was to determine the plasma levels of the triiodothyronine (T-3) and thyroxine (T-4), in six Ideal ewe sheeps during seasonal anoestrus, by radioimmunoassay. The blood samples were collected from the jugular vein catheter over a period of 24 hours, at 2-h intervals (12, 14, 16, IX, 20, 22, 24, OZ, 04, 06, OX, and 10 hours). II was used analysis of variance for data adjustments, and the decomposition of the collected periods in non-orthogonal polynomial. It was observed a crescent linear effect of the T-4 plasma levels, presenting lower level of 49.60+/-11.41 and higher level of 76.99+/-10.0 ng/ml, at fourth and last blood samples collection, respectively. T-3 plasma levels showed a significant cubic response during 24 hours, with the highest value of 0.94+/-0.20 ng/ml at the end of the the study. In conclusion, thyroidal hormones levels were lower in the first blood samples collection, increasing progressively during the night, reaching the highest levels at the morning period.